Electric Vehicles - Paving the Road to Widespread Adoption: A Review of Technical and Non-technical Challenges - Rahul Gaikwad; Akash Tomar (International Journal of Robotics and Automation in Mechanics, 2024)
Electric vehicles (EVs) have gained significant interest in recent years as a sustainable transportation method to reduce greenhouse gas emissions. However, the adoption of EVs faces several technological and economic challenges that need to be addressed. This review provides a comprehensive overview of the current state of the art in EV technologies including batteries, power electronics, motors, and charging systems. The key challenges inhibiting widespread EV adoption are discussed including driving range, battery cost, charging infrastructure, and safety issues. The latest research aimed at overcoming these barriers is highlighted. Battery technologies like lithium-ion, lithium sulfur, and solid-state batteries are compared in terms of cost, safety, energy density, and charging rates. The role of smart grids and vehicle-to-grid integration for EVs is explored. Government policies and regulatory mechanisms required to facilitate the transition to EVs are also examined. This review concludes by synthesizing promising directions for future work to enable EVs to effectively serve as an eco-friendly transportation alternative.
Keywords: charging infrastructure; driving range; electric vehicles; lithium-ion batteries; vehicle-to-grid